Knowledge Levels of Pediatric Intensive Care Staff About Delirium, Single Center Experience - Emel Uyar; Serhat Emeksiz; Oktay Perk; Serhan Özcan; Ahmet Ertürk; Elif Emel Erten; Süleyman Arif Bostancı; Müjdem Nur Azılı (Journal of Pediatric Emergency and Intensive Care Medicine)

(untitled)
Introduction:Delirium is frequently encountered in pediatric intensive care units (PICUs) in critical patients and is characterized by fluctuating acute impaired awareness and cognition. An inadequate level of knowledge in critical care staff can bring about a significant risk that would delay diagnosis and treatment. This study investigated the delirium knowledge of PICU staff.Methods:This was a single-center, cross-sectional, descriptive survey study. A 17-item online questionnaire was administered to PICU staff who worked in the PICU, surgery PICU and burn PICU.Results:We invited 120 PICU staff to the study, and 88% (n=106) responded to the questionnaire. Of the responders, 30% had an inadequate level of knowledge regarding hypoactive delirium, 57% inaccurately chose the Glasgow-Coma score as the appropriate screening tool for delirium, 80% incorrectly responded that benzodiazepines were used in the treatment of delirium, and 79% thought that patients did not remember their moments of delirium.Conclusion:The results indicated that PICU staff required training on the importance, risk factors, diagnosis, and treatment of pediatric delirium. The lack of a screening tool in the native language further complicates the assessment of delirium. PICU staff equipped with improved knowledge and the appropriate screening tools can make a difference in recognizing, preventing, and proper treatment of pediatric delirium.